PENGETAHUAN SEBAGAI PREDISPOSISI PERILAKU KESELAMATAN DAN KESEHATAN KERJA - I Gede Purnawinadi (Fakultas Ilmu Keperawatan Universitas Advent Indonesia, 2019)
Occupational Safety and Health (K3) is pursued to achieve the optimum degree of workforce health to achieve labor welfare and to increase work productivity. Knowledge of OHS in a project becomes a basic requirement related to the potential risk of workplace accidents in the execution of work. This study aims to determine the relationship of knowledge with K3 behavior to workers on the Toll Road in Lembean. The research design used in this study was an analytical survey with a cross sectional approach. The research sample was 248 respondents using purposive sampling technique from the population. The results of the study found that the dominant toll road workers in Lembean (96.8%) had good knowledge and behavior with very good categories (85.5%). Based on the results of data analysis obtained p value = 0.004 <0.05 means that there is a significant relationship between knowledge and behavior of occupational safety and health on toll road workers in Lembean, with very weak closeness at 0.184 and positive pattern correlation coefficient, where the better the knowledge someone, the behavior about occupational safety and health is getting better. It is recommended for future researchers to develop this research by reviewing other factors such as attitude, how to use personal protective equipment. Keywords: nowledge, Behavior, Safety and Occupational Health.